Peran teknik CBT (Cognitive Behavior Therapy) dalam mengelola stres remaja - Zuraidah Zuraidah (STIKes Ibnu Sina Ajibarang, 2023)
The rapid increase in emotional levels during early adolescence is known as a period of storm and stress. So parents complain and find it difficult to deal with teenagers, in this transition period. This emotional growth is the result of physical changes, especially the hormones of adolescence. If it is related to social conditions, this increased emotional level is a sign that teenagers are experiencing conditions that are different from previous times. This condition triggers teenagers to become stressed and confused. Adolescence is a transition period, so the counselees studied were teenagers who experienced feelings of anxiety due to the confusion experienced by the absence of the father's role, making the counselees stressed, emotional and demanding a lot of attention from their parents, fighting, disobeying and resulting in decreased concentration in learning. The OV counselor, a 12 year old male teenager, was given the CBT (Cognitive Behavior Therapy) technique. Cognitive therapy helps the counselor learn to recognize mistakes and change them. Apart from positive thinking, cognitive therapy is also related to happy thinking. Behavioral therapy helps link problematic situations and habits of responding to problems. Clients learn to change their behavior, calm their mind and body to feel better, think more clearly and help them make the right decisions. understand thought patterns by showing empathy so that you feel expected to be present with love and attention.